Respuesta :
a = 1 b = 9 c = 10
x = [-b +- sq root(b^2 -4*a*c)] / 2*a
x = [-9 +- sq root (81 -40) ] / 2
x = -9 /2 + sq root (41) / 2
x = -4.5 + 3.202
= -1.298
x = -4.5 - 3.202
= -7.702
answer is B
x = [-b +- sq root(b^2 -4*a*c)] / 2*a
x = [-9 +- sq root (81 -40) ] / 2
x = -9 /2 + sq root (41) / 2
x = -4.5 + 3.202
= -1.298
x = -4.5 - 3.202
= -7.702
answer is B
The solutions to the equation are -7.7 and -1.3 option (B) is correct.
What is a quadratic equation?
Any equation of the form [tex]\rm ax^2+bx+c=0[/tex] where x is variable and a, b, and c are any real numbers where a ≠ 0 is called a quadratic equation.
We have a quadratic equation:
[tex]\rm x^2+9x+10=0[/tex]
Comparing with the standard form of a quadratic equation, we get:
a = 1, b = 9, and c = 10
We know the formula for finding the roots of a quadratic equation:
[tex]\rm x = \frac{-b\pm\sqrt{b^2-4ac} }{2a}[/tex]
Putting the values of the a, b, and c in the formula, we get:
[tex]\rm x = \frac{-9\pm\sqrt{9^2-4(1)(10)} }{2\times1}[/tex]
[tex]\rm x = \frac{-9\pm\sqrt{81-40} }{2}\\\\\rm x = \frac{-9\pm\sqrt{41} }{2}[/tex]
Taking the plus sign first:
[tex]\rm x = \frac{-9+\sqrt{41} }{2} \Rightarrow -1.298 \approx -1.3[/tex]
Now taking the negative sign:
[tex]\rm x = \frac{-9-\sqrt{41} }{2} \Rightarrow -7.7015 \approx -7.7[/tex]
Thus, the solutions to the equation are -1.3 and -7.7 option (B) is correct.
Learn more about quadratic equations here:
brainly.com/question/2263981